Loss of filamentous actin, tight junction protein expression, and paracellular barrier integrity in frataxin-deficient human brain microvascular endothelial cells—implications for blood-brain barrier physiology in Friedreich’s ataxia - Smith, Frances M.; Kosman, Daniel J. (Frontiers in Molecular Biosciences, 2024)
Introduction: Friedreich’s Ataxia (FRDA) is the most prevalent inherited ataxia. FRDA results from loss of Frataxin (FXN), an essential mitochondrial iron trafficking protein. FRDA starts with an early burst of neurodegeneration of the dorsal root ganglion and cerebellar dentate nuclei, followed by progressive brain iron accumulation in the latter. End stage disease includes cardiac fibrosis that contributes to hypertrophic cardiomyopathy. The microvasculature plays an essential barrier role in both brain and heart homeostasis, thus an investigation of this tissue system in FRDA is essential to the delineation of the cellular dysfunction in this genetic disorder. Previous reports have identified cytoskeletal alterations in non-barrier forming FRDA cell models, but physiological consequences are limited. Methods: We investigated brain microvascular endothelial cell integrity in FRDA in a model of the blood-brain barrier (BBB). We have knocked down FXN in immortalized human brain microvascular endothelial cells (hBMVEC), which compose the microcapillaries of the BBB, by using shRNA. We confirmed known cellular pathophysiologies of FXN-knockdown including decreased energy metabolism, markers of oxidative stress, and increased cell size. Results: We investigated cytoskeletal architecture, identifying decreased filamentous actin and Occludin and Claudin-5 tight junction protein expression in shFXN hBMVECs. This was consistent with decreased transendothelial electrical resistance (TEER) and increased paracellular tracer flux during early barrier formation. shFXN hBMVEC start with only 67% barrier integrity of the controls, and flux a paracellular tracer at 800% of physiological levels. Discussion: We identified that insufficient FXN levels in the hBMVEC BBB model causes changes in cytoskeletal architecture and tight junction protein abundance, co-incident with increased barrier permeability. Changes in the integrity of the BBB may be related to patient brain iron accumulation, neuroinflammation, neurodegeneration, and stroke. Furthermore, our findings implicate other barrier cells, e.g., the cardiac microvasculature, loci of disease pathology in FRDA.